(untitled) (MIST International Journal of Science and Technology, 2025)
Agar, a natural biopolymer extracted from red algae, holds immense potential for revolutionizing healthcare, including biomedical engineering. This study explores the extraction feasibility of agar from red algae (Gracilaria tenuistipitata) abundantly available in the coastal area of Cox’s Bazar, Bangladesh. Five extraction methods were investigated, including a control group and treatments with water and NaOH solutions at concentrations of 2%, 4%, and 6%. The extraction of agar from algae was characterized through Fourier-transform infrared spectroscopy (FTIR), gel strength testing, melting and gelling temperature assessments, pH value measurement, and sulfate content analysis. Statistical analysis, including ANOVA and Tukey’s HSD test, was utilized to assess the impact of the pre-treatment process on the yield and characteristics of agar. The test revealed significant variations among the different extraction methods (p < 0.05), highlighting the crucial role that pre-treatment plays in influencing agar yield and its physicochemical properties. While the control group achieved the highest agar yield (16.67 ± 1.44%), the 2% NaOH pre-treatment showed superior physicochemical attributes. Specifically, this treatment resulted in agar with optimal gel strength (3.25 ± 0.67 N/cm²), melting temperature (84.20 ± 0.80°C), gelling temperature (36.13 ± 1.21°C), pH (7.49 ± 0.26), and sulfate content (3.67 ± 0.58 mg/L), all of which are comparable to those of commercial agar. This preliminary study suggests that the red algae (Gracilaria tenuistipitata) found in Bangladesh is a promising source of agar for wider applications, including biomedical engineering. The agar extracted from abundant local sources in this country could unlock its potential for advancing healthcare solutions and sustainable national economic growth. MIJST, V. 13,December 2025: 27-38 https://doi.org/10.47981/j.mijst.13(02)2025.536(27-38)